DNA methylation pattern of Photoperiod‐B1 is associated with photoperiod insensitivity in wheat (Triticum aestivum). Issue 3 (31st July 2014) - Sun, Han; Guo, Zhiai; Gao, Lifeng; Zhao, Guangyao; Zhang, Wenping; Zhou, Ronghua; Wu, Yongzhen; Wang, Haiyang; An, Hailong; Jia, Jizeng
Summary: As one of the three key components of the 'Green Revolution', photoperiod insensitivity is vital for improved adaptation of wheat ( Triticum aestivum ) cultivars to a wider geographical range. Photoperiod‐B1a ( Ppd‐B1a ) is one of the major genes that confers photoperiod insensitivity in 'Green Revolution' varieties, and has made a significant contribution to wheat yield improvement. In this study, we investigated the mechanisms underlying the photoperiod insensitivity of Ppd‐B1a alleles from an epigenetic perspective using a combination of bisulfite genomic sequencing, orthologous comparative analysis, association analysis, linkage analysis and gene expression analysis. Based on the study of a large collection of wheat germplasm, we report two methylation haplotypes of Ppd‐B1 and demonstrate that the higher methylation haplotype (haplotype a) was associated with increased copy numbers and higher expression levels of the Ppd‐B1 gene, earlier heading and photoperiod insensitivity. Furthermore, assessment of the distribution frequency of the different methylation haplotypes suggested that the methylation patterns have undergone selection during the wheat breeding process. Our study suggests that DNA methylation in the regulatory region of the Ppd‐B1 alleles, which is closely related to copy number variation, plays a significant role in wheat breeding, to confer photoperiod insensitivity and better adaptation to a wider geographical range.